Taxonomic reassessment of Helicopsis austriaca Gittenberger, 1969 and its relationships to H. striata (O.F. Müller, 1774) and H. hungarica (Soos & H. Wagner, 1935) (Eupulmonata: Helicoidea). (22nd September 2018) - Duda, Michael; Haring, Elisabeth; Bieringer, Georg; Eschner, Anita; Mrkvicka, Alexander; Mason, Katharina
Abstract: The taxonomic status of the Austrian endemic Helicopsis austriaca has changed several times since its first description. Originally described at species level, it was later treated as a subspecies of H. striata or more usually as a junior synonym of the latter species. The same applies to H. hungarica . Despite the unclear taxonomy of these taxa, H. austriaca is listed in the Annex II of the European Union Habitats Directive as a species of 'community interest'. To clarify the taxonomic status of these taxa, an integrative study was conducted comparing the molecular systematics, morphology and biogeography of Helicopsis populations in eastern Austria and adjacent areas. Mitochondrial sequences confirmed H. austriaca, H. hungarica and H. striata as distinct clades. The nuclear histone 4 gene sequences provided a less clear picture. Shell measurements allowed an unambiguous separation of H. austriaca from H. hungarica, but only a partial separation of either taxon from H. striata . While some individuals of H. austriaca have a more globular external shape of the penis than in the other two taxa, detailed sections of the penis revealed an unambiguous separation of the three taxa. On the basis of these data we confirm the species-level status of H. austriaca and H. hungarica . Helicopsis austriaca was confirmed to be an endemic of Lower Austria and a hitherto unknown differentiation of this species into two geographic groups was detected. One group comprises specimens from the type locality and other dry grassland localities (predominately edaphic steppe) in the Viennese Basin; the shells are smaller and can easily be separated from H. striata and H. hungarica without dissection. The other group lives in patches of treeless rock steppe within the primary pine forests of the Northern Limestone Alps and shows some overlap with H. striata in shell dimensions. Helicopsis hungarica is an eastern sand-steppe dweller with a patchy and poorly known distribution, broadly sympatric with H. striata. Helicopsis hungarica is currently known from Hungary, one locality in Austria and probably at one locality in western Russia. Helicopsis striata, on the other hand, is a more northerly distributed taxon, which probably colonized the study area from the north, dispersing southwards along the River Morava to northern Burgenland, southern Slovakia and northwestern Hungary. Study of published sequence data from the eastern parts of the ranges of H. striata and H. hungarica suggest that both require more comprehensive and integrative research.